COOPERATIVE PRINCIPLE THAT USE BY MR. HARVEY ON LITTLE BIG SHOTS TALK SHOW - BERLIANA ANJELA PUTRI (English Language, Linguistics, Literature, And Education Journal, 2025)
Even though conversations between adults and children are considered unable to fulfill the principles of cooperation, it turns out that in the conversations between adults and children at this talk show, many of the principles of cooperation in good conversation are found. The research aims to analyze the maxims detected in the conversation, and to know the procedures for building a good relationship in the conversation held by the presenter. Therefore, this research uses the theory put forward by Grice (1975) regarding cooperative principles which discusses maxims. For research data, researchers used five YouTube channel videos from Little Big Shots talk show UK. To make it easier for researchers to answer these problems, researchers used qualitative research with descriptive methods. Data collection techniques include non-participant listening, recording, taking notes. The data analysis technique for this research is descriptive technique. Research results (1) The types of maxims detected in twenty-five conversations were eight quality maxims, eleven quantity maxims, five relevant maxims, one manner maxim. (2) Mr. Harvey builds positive relationships when speaking by using the concept of rationality, composing questions using narrative discourse, and creating excitement by adding elements of comedy.